GMAT Question of the Day - Daily to your Mailbox; hard ones only

It is currently 16 Oct 2019, 23:06

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

The (x, y) pair (-1, 1) satisfies which of the following equations?

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Find Similar Topics 
Retired Moderator
avatar
V
Joined: 22 Jun 2014
Posts: 1093
Location: India
Concentration: General Management, Technology
GMAT 1: 540 Q45 V20
GPA: 2.49
WE: Information Technology (Computer Software)
GMAT ToolKit User
The (x, y) pair (-1, 1) satisfies which of the following equations?  [#permalink]

Show Tags

New post 17 Nov 2018, 10:38
2
00:00
A
B
C
D
E

Difficulty:

  5% (low)

Question Stats:

80% (00:47) correct 20% (00:54) wrong based on 194 sessions

HideShow timer Statistics

The \((x, y)\) pair \((-1, 1)\) satisfies which of the following equations?

I. \(2x^3 - y^2 = -3\)
II. \(2x^2 - y^3 = 1\)
III. \(x^2 - 2y^3 = -1\)

(A) I only
(B) I and II only
(C) I and III only
(D) II and III only
(E) I, II, and III


Project PS Butler : Question #24


Subscribe to get Daily Email - Click Here | Subscribe via RSS - RSS

_________________
Manager
Manager
avatar
P
Joined: 01 Mar 2015
Posts: 69
Re: The (x, y) pair (-1, 1) satisfies which of the following equations?  [#permalink]

Show Tags

New post 17 Nov 2018, 11:03
1
HKD1710 wrote:
The \((x, y)\)pair \((-1, 1)\) satisfies which of the following equations?

I. \(2x^3 - y^2 = -3\)
II. \(2x^2 - y^3 = 1\)
III. \(x^2 - 2y^3 = -1\)

(A) I only
(B) I and II only
(C) I and III only
(D) II and III only
(E) I, II, and III


Putting x = -1 and y = 1 in all equations
I. \(2x^3 - y^2 = -3\)
=> -2 - 1 = -3
=> -3 = -3
Satisfy

II. \(2x^2 - y^3 = 1\)
=> 2 - 1 = 1
=> 1 = 1
Satisfy

III. \(x^2 - 2y^3 = -1\)
=> 1 - 2 = -1
=> -1 = -1
Satisfy

All equations are satisfied

Answer choice (E)

Posted from my mobile device
VP
VP
User avatar
D
Joined: 09 Mar 2016
Posts: 1230
Re: The (x, y) pair (-1, 1) satisfies which of the following equations?  [#permalink]

Show Tags

New post 17 Nov 2018, 11:21
\((-1, 1)\)

I. \(2 (1-)^3 - 1^2 = -3\) ---> -2-1 = -3 YES
II. \(2x^2 - y^3 = 1\) ----> 2(1)- 1 =1 YES
III. \(x^2 - 2y^3 = -1\) ----> 1 -2 (1) = -1 YES


E
Manager
Manager
User avatar
S
Joined: 21 Jul 2018
Posts: 186
Reviews Badge
The (x, y) pair (-1, 1) satisfies which of the following equations?  [#permalink]

Show Tags

New post 23 Jan 2019, 07:23
HKD1710 wrote:
The \((x, y)\) pair \((-1, 1)\) satisfies which of the following equations?

I. \(2x^3 - y^2 = -3\)
II. \(2x^2 - y^3 = 1\)
III. \(x^2 - 2y^3 = -1\)

(A) I only
(B) I and II only
(C) I and III only
(D) II and III only
(E) I, II, and III


Project PS Butler : Question #24


Subscribe to get Daily Email - Click Here | Subscribe via RSS - RSS


Hi HKD1710

why in equation

I. \(2x^3 - y^2 = -3\)

\(- y^2\) = -1 and not +1?

I know there is some reason behind that but don't know what it is. Could you please assist.
_________________
______________________________
Press +1 Kudos if my post helped you a little and help me to ulcock the tests ;) Wish you all success

I'd appreciate learning about the grammatical errors in my posts


Please let me know if I'm wrong somewhere and help me to learn :-)
Retired Moderator
avatar
V
Joined: 22 Jun 2014
Posts: 1093
Location: India
Concentration: General Management, Technology
GMAT 1: 540 Q45 V20
GPA: 2.49
WE: Information Technology (Computer Software)
GMAT ToolKit User
Re: The (x, y) pair (-1, 1) satisfies which of the following equations?  [#permalink]

Show Tags

New post 23 Jan 2019, 11:56
Gmatprep550 wrote:
HKD1710 wrote:
The \((x, y)\) pair \((-1, 1)\) satisfies which of the following equations?

I. \(2x^3 - y^2 = -3\)
II. \(2x^2 - y^3 = 1\)
III. \(x^2 - 2y^3 = -1\)

(A) I only
(B) I and II only
(C) I and III only
(D) II and III only
(E) I, II, and III


Project PS Butler : Question #24


Subscribe to get Daily Email - Click Here | Subscribe via RSS - RSS


Hi HKD1710

why in equation

I. \(2x^3 - y^2 = -3\)

\(- y^2\) = -1 and not +1?

I know there is some reason behind that but don't know what it is. Could you please assist.


\(y=1\)

\(y^2 = 1^2\)

\(y^2 = 1\)

\(- y^2 = - 1\)
_________________
Manager
Manager
User avatar
S
Joined: 21 Jul 2018
Posts: 186
Reviews Badge
Re: The (x, y) pair (-1, 1) satisfies which of the following equations?  [#permalink]

Show Tags

New post 23 Jan 2019, 22:17
HKD1710 wrote:
Gmatprep550 wrote:
HKD1710 wrote:
The \((x, y)\) pair \((-1, 1)\) satisfies which of the following equations?

I. \(2x^3 - y^2 = -3\)
II. \(2x^2 - y^3 = 1\)
III. \(x^2 - 2y^3 = -1\)

(A) I only
(B) I and II only
(C) I and III only
(D) II and III only
(E) I, II, and III


Project PS Butler : Question #24


Subscribe to get Daily Email - Click Here | Subscribe via RSS - RSS


Hi HKD1710

why in equation

I. \(2x^3 - y^2 = -3\)

\(- y^2\) = -1 and not +1?

I know there is some reason behind that but don't know what it is. Could you please assist.


\(y=1\)

\(y^2 = 1^2\)

\(y^2 = 1\)

\(- y^2 = - 1\)



But \(- y^2\) also = - y * - y =- 1 * - 1 which = + 1 hence would like to know when to follow above method described by you. I am sure we will follow that if \(y^2\) would have provided in bracket for ex \(-(y^2)\)

Hope you are getting where I am getting confused.

Thanks !
_________________
______________________________
Press +1 Kudos if my post helped you a little and help me to ulcock the tests ;) Wish you all success

I'd appreciate learning about the grammatical errors in my posts


Please let me know if I'm wrong somewhere and help me to learn :-)
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 58391
The (x, y) pair (-1, 1) satisfies which of the following equations?  [#permalink]

Show Tags

New post 23 Jan 2019, 22:22
Gmatprep550 wrote:
HKD1710 wrote:
Gmatprep550 wrote:
The \((x, y)\) pair \((-1, 1)\) satisfies which of the following equations?

I. \(2x^3 - y^2 = -3\)
II. \(2x^2 - y^3 = 1\)
III. \(x^2 - 2y^3 = -1\)

(A) I only
(B) I and II only
(C) I and III only
(D) II and III only
(E) I, II, and III



Hi HKD1710

why in equation

I. \(2x^3 - y^2 = -3\)

\(- y^2\) = -1 and not +1?

I know there is some reason behind that but don't know what it is. Could you please assist.


\(y=1\)

\(y^2 = 1^2\)

\(y^2 = 1\)

\(- y^2 = - 1\)



But \(- y^2\) also = - y * - y =- 1 * - 1 which = + 1 hence would like to know when to follow above method described by you. I am sure we will follow that if \(y^2\) would have provided in bracket for ex \(-(y^2)\)

Hope you are getting where I am getting confused.

Thanks !


No. \(-y^2=-(y*y)\). On the other hand \((-y)*(-y) = y^2\).
_________________
Manager
Manager
User avatar
S
Joined: 21 Jul 2018
Posts: 186
Reviews Badge
Re: The (x, y) pair (-1, 1) satisfies which of the following equations?  [#permalink]

Show Tags

New post 23 Jan 2019, 22:32
I am wondering why \(-1^2 = +1\) where as \(-Y^2 = -(Y*Y)\)?
_________________
______________________________
Press +1 Kudos if my post helped you a little and help me to ulcock the tests ;) Wish you all success

I'd appreciate learning about the grammatical errors in my posts


Please let me know if I'm wrong somewhere and help me to learn :-)
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 58391
Re: The (x, y) pair (-1, 1) satisfies which of the following equations?  [#permalink]

Show Tags

New post 23 Jan 2019, 23:15
1
GMAT Club Legend
GMAT Club Legend
User avatar
D
Joined: 18 Aug 2017
Posts: 5009
Location: India
Concentration: Sustainability, Marketing
GPA: 4
WE: Marketing (Energy and Utilities)
GMAT ToolKit User Premium Member
Re: The (x, y) pair (-1, 1) satisfies which of the following equations?  [#permalink]

Show Tags

New post 23 Jan 2019, 23:28
simply plugin for x,y (-1,1) ; all options are valid
IMO E

HKD1710 wrote:
The \((x, y)\) pair \((-1, 1)\) satisfies which of the following equations?

I. \(2x^3 - y^2 = -3\)
II. \(2x^2 - y^3 = 1\)
III. \(x^2 - 2y^3 = -1\)

(A) I only
(B) I and II only
(C) I and III only
(D) II and III only
(E) I, II, and III


Project PS Butler : Question #24


Subscribe to get Daily Email - Click Here | Subscribe via RSS - RSS
GMAT Club Bot
Re: The (x, y) pair (-1, 1) satisfies which of the following equations?   [#permalink] 23 Jan 2019, 23:28
Display posts from previous: Sort by

The (x, y) pair (-1, 1) satisfies which of the following equations?

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  





Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne